ANALISIS PROFITABILITAS, FIRM SIZE DAN STRUKTUR KEPEMILIKAN SAHAM TERHADAP INTELLECTUAL CAPITAL DISCLOSURE DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN PADA SEKTOR MAKANAN DAN MINUMAN TAHUN 2010-2015 - Aisyah Margie, Lyandra (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This research aims to analyze the effect of profitability, firm size and shareholding structure on intellectual capital disclosure and its impact on company value in food and beverage sub-sector listed in Indonesia Stock Exchange. The sample in this research is food and beverage sub-sector companies listed in Indonesia Stock Exchange period 2010-2015 period. By using purposive sampling method, obtained as many as 11 companies determined as sample research. Statistical test is done by using regression test of panel data of random effect model. The research method used is quantitative descriptive by doing the activity of collecting secondary data from annual report of company. The results showed that simultaneously, profitability, firm size and share ownership have significant effect on intellectual capital disclosure. Partially, firm size variables significantly influence intellectual capital disclosure but profitability and share ownership have no significant effect on intellectual capital disclosure. While intellectual capital disclosure has a significant effect on company value